2014
DOI: 10.1038/ki.2013.289
|View full text |Cite
|
Sign up to set email alerts
|

AMG 416 (velcalcetide) is a novel peptide for the treatment of secondary hyperparathyroidism in a single-dose study in hemodialysis patients

Abstract: AMG 416 (velcalcetide), a novel peptide agonist of the calcium-sensing receptor, lowers plasma parathyroid hormone in preclinical uremic animal models and in normal healthy individuals. Here, we studied its efficacy in hemodialysis patients suffering from secondary hyperparathyroidism. Major inclusion criteria were hemodialysis for at least 3 months, serum parathyroid hormone over 300 pg/ml, a corrected serum calcium of 9.0 mg/dl or more, and stable doses of vitamin D analogs for at least 3 weeks prior to scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 31 publications
(37 reference statements)
4
61
0
4
Order By: Relevance
“…for sHPT or in patients intolerant of or nonresponsive to oral or intravenous active vitamin D analogs and/or cinacalcet (22,23). Although many studies have highlighted the risks associated with sHPT, relatively few published studies have reported risks associated with the parathyroidectomy procedure itself.…”
Section: Discussionmentioning
confidence: 96%
“…for sHPT or in patients intolerant of or nonresponsive to oral or intravenous active vitamin D analogs and/or cinacalcet (22,23). Although many studies have highlighted the risks associated with sHPT, relatively few published studies have reported risks associated with the parathyroidectomy procedure itself.…”
Section: Discussionmentioning
confidence: 96%
“…AMG 416 acts in a fashion similar to the phenylalkylamine CaSR agonist, cinacalcet (Sensipar/Mimpara; Amgen Inc.) by decreasing circulating levels of parathyroid hormone (PTH), calcium, and phosphorus in dialysis patients with secondary HPT (Block et al, 2004;Lindberg et al, 2005;Moe et al, 2005;Martin et al, 2014b;Bell et al, 2015). However, AMG 416 differs from cinacalcet in its chemical class, intravenous route of administration, extended half-life, and thrice weekly dosing following each hemodialysis session (Martin et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, cinacalcet is currently indicated for the treatment of SHPT in dialysis patients and is shown to reduce hypercalcemia in patients with parathyroid carcinoma and in selected cases of primary hyperparathyroidism (34,35). AMG-416 is currently in development and represents a novel, third-generation intravenous long-acting selective peptide agonist of the CaR (36,37).…”
Section: Calcimimetic and Cinacalcet Generalitiesmentioning
confidence: 99%